Does leukocyte-poor or leukocyte-rich platelet-rich plasma applied with biopolymers have superiority to conventional platelet-rich plasma applications on chondrocyte proliferation? - Yaşar Şirin, Duygu; Yılmaz, İbrahim; İşyar, Mehmet; Öznam, Kadir; Mahiroğulları, Mahir (Turkish Joint Diseases Foundation, 2017)
Objectives: This study aims to investigate the possible effects of leukocyte concentration in the content of platelet-rich plasma (PRP) and the administration of PRP using a drug delivery system on chondrocyte proliferation in vitro conditions. Patients and methods: Blood from nine male patients (mean age 65 years; range 49 to 81 years) with advanced stage osteoarthritis who had not responded to medical or conservative treatments and underwent total knee arthroplasty was used to prepare two formulations: PRP with low concentration leukocytes (2000-4000 leukocytes/mu L) was designated as pure PRP (P-PRP), whereas PRP with high concentration leukocytes (9000-11000 leukocytes/mu L) as leukocyte-rich PRP (L-PRP). Samples were divided into five groups as control group (group 1), chondrocyte cultures with P-PRP applied directly (group 2), chondrocyte cultures with L-PRP applied directly (group 3), chondrocytes co-cultured with P-PRP applied hydrogel (group 4), and chondrocytes co-cultured with L-PRP applied hydrogel (group 5). In all groups; cell morphology, viability and proliferation were compared with the expression of stage-specific embryonic antigen-1 (SSEA-1), a precondrocyte marker. Results: Maximum cell proliferation and SSEA-1 expression occurred in group 4, with a statistically significant correlation between SSEA-1 expression and cell proliferation. Conclusion: Our study showed the importance of leukocyte concentration of PRP and efficiency of delivery systems such as hydrogel and that L-PRP administered with a delivery system is more efficient than conventional applications of PRP in the treatment of cartilage damage.
Biyopolimerler ile uygulanan lökositten fakir veya lökositten zengin trombositten zengin plazmanın kondrosit proliferasyonunda konvansiyonel trombositten zengin plazma uygulamalarına üstünlüğü var mıdır?
WOS: 000415126000002
PubMed ID: 29125811
Keywords: Co-Culture Techniques; Hydrogel; Platelet-Rich Plasma; Stage-Specific Embryonic Antigens